Four-week Oral Toxicity Studies of the New Quinolone Antibacterial Agent Cetefloxacin Tosylate in Rats and Marmoset Monkeys - Guzmán, Antonio; Garcia, Concepción; Marin, Ana Paz; Demestre, Isabel (Arzneimittelforschung, 2001)
Four-week oral toxicity studies with cetefloxacin tosylate ((-)-7[3-(R)-amino-2-(S)-methyl-1 -azetidinyl] -1-(2,4-dlfluorophenyi)-1,4-dihydro-6-fluoro-4-oxo-3-qunolinecarboxylic acid tosylate, CAS 141725-88-4 (base), E-4868.Ts) a new quinolone antibacterial agent, were performed in Sprague-Dawley rats and marmoset monkeys at doses of 100, 450, 2000 mg/kg/d and 25, 50, 125, 300 mg/ kg/d, respectively. In rats, due to its toxicity the high dose was decreased to 1000 mg/kg/d after 3 days of treatment. Mortality was recorded among high dose rats receiving 2000 or 1000 mg/kg/d. Rats receiving dosages of 450 or 2000/1000 mg/ kg/d showed less activated mandibular lymph nodes, cortical lymphocyte depletion of mandibular and/or mesenteric lymph nodes, atrophy of the white pulp of the spleen, cortical atrophy of thymus and thymic apoptosis. Enlarged caeca, increased water consumption and variations in plasma electrolyte levels were observed in animals receiving these dosages and in male rats receiving 100 mg/kg/d. Low neutrophil counts were observed in rats receiving dosages of 100 or 450 mg/kg/d, and increased alkaline phosphatase and alanine transaminase plasma levels and slightly decreased plasma protein levels in females receiving 450 or 2000/1000 mg/kg/d. Marmosets receiving dosages of 50 mg/kg/d and above displayed several clinical signs which included emesis, diarrhoea, ptosis, occasional episodes of under- and overactivity, and excessive scratching activity. Skin reddening was observed during the first week of treatment in marmosets receiving 300 mg/kg/d.On the basis of the results obtained it can be concluded that the non-toxic doses of E-4868.Ts after 4-week oral administration in rats and marmoset monkeys were 100 and 25 mg/kg/d, respectively.
Keywords: Antibacterials; CAS 141725-88-4; Cetefloxacin tosylate, marmoset monkey, rat, toxicity study; E-4868.Ts; Quinolones